Les réactions de la doctrine à la création du droit par les juges : le droit des entreprises - Antaki, Nabil (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper attempts to survey the present state of the law and current trends in legal literature as regards the concept of enterprise in Quebec law. The legal concept of enterprise does not carry the same meaning for all legal scholars in Quebec. A more traditional group restricts it to cases where some type of legal entity is created as a subject of rights and liabilities. A modernist group is prepared to give legal recognition to the enterprise as the basic economic unit, having rights and duties on a broad societal scale. This latter approach, closer to the realities of economics, is obviously followed in federal and Quebec legislation, whether protective or interventionist, with the result that conflicting definitions of the enterprise have been used for many different purposes. Through an increasing body of published writings, Quebec legal scholars have been contributing to the rationalization and harmonization of commercial law in relation to the concept of enterprise. Judicial adherence to traditional views has sometimes prevented or slowed down the implementation of rules suggested by scholars. In some cases, though, bold judicial pronouncements have met with unqualified approval from the writers. In certain areas, administrative bodies such as regulatory agencies have clearly outdone the regular courts at creative and effective law-making. In spite of shortcomings on the part of legal writers, legislators and judges, a concept of enterprise is gradually emerging as the key element in the development of a more realistic system of commercial law.